A Capabilitarian Participatory Paradigm: Methods, Methodologies and Cosmological Issues and Possibilities. Issue 1 (2nd January 2022) - Martinez-Vargas, Carmen; Walker, Melanie; Melis Cin, F.; Boni, Alejandra
ABSTRACT: Meaningful participation of people as agents in development practice has been a central concern in capabilitarian scholarship and of Amartya Sen's own work, as a valuable freedom and functioning in itself. Yet, there has been limited attention until now about knowledge generation processes and who is fully included, despite a growing body of literature arguing for pluriversality and decolonial approaches against historical and geographical inequalities at many levels. The paper proposes that capabilitarian scholarship could be enriched by considering a pluriverse of methodological perspectives, building on the work already undertaken but taking it further to create multi-epistemic conversations. This paper explores why the methodological and cosmological – onto-epistemological – unexplored areas of participatory research in capabilitarian scholarship should be embedded in our research culture and practice for more inclusive, decolonial, methodologically challenging empirical strategies (beyond methods and methodologies) that will place those situated at the margins of epistemic divisions and conflicts in the centre of knowledge production and debates. To this end and adding to the debates, the paper first considers participatory projects reported on in the journal before presenting an original framing of a capabilitarian participatory paradigm. The paper further proposes some principles that underpin its operationalisation.